Teacher–Child Interactions in Chile and Their Associations With Prekindergarten Outcomes. Issue 3 (27th January 2015) - Leyva, Diana; Weiland, Christina; Barata, M.; Yoshikawa, Hirokazu; Snow, Catherine; Treviño, Ernesto; Rolla, Andrea
<x xml:space="preserve">Abstract</x> Quality of teacher–child interactions is central to prekindergarten children's learning. In the United States, the quality of teacher–child interactions is commonly assessed using the teaching through interactions conceptual framework and an associ/ated observational tool, the Classroom Assessment Scoring System (CLASS). This study examined: (a) whether there was evidence supporting three distinctive domains of teacher–child interactions in Chile (construct validity) and (b) whether these domains predicted end‐of‐prekindergarten language, academic, and executive function skills in Chile (predictive validity). The sample consisted of 91 Chilean prekindergarten classrooms (1, 868 four‐year‐old children). The findings support both construct and predictive validity of the teaching through interactions conceptual framework as assessed by the CLASS in Chile. Implications for cross‐country comparison of quality of teacher–child interactions in prekindergarten classrooms are discussed.